DESIGN OF PERFORMANCE MEASUREMENT SYSTEM IN PUSPEKNUBIKA KODIKLATAL - Tony Herdyanto; Avando Bastari; Eko Krisdiono (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2021)
The success or success of an organization is achieved because of the ability of the organization in carrying out its vision and mission as expected, as it is known that one of the objectives of the process of organizing the functions of government is the guarantee of national security and welfare conditions for all its people. The purpose of the research was to obtain measurements of organizational performance by BSC method in Puspeknubika Kodiklatal Surabaya. In the test of variable validity of customer satisfaction level in service attributes for comfort criteria as much as 67.3%, criteria of ability to meet the needs as much as 71.7%, health and safety criteria as much as 65.1%, criteria of ability to provide the required information as much as 84.4% and good communication criteria as much as 65%. Balanced Scorecard (BSC) method can be applied to government and military organizations, especially in this case Puspeknubika Kodiklatal Surabaya, because with this method all aspects can be measured and known performance. Keyword : Performance measurement, Balance Scorecard, Puspeknubika